PELATIHAN PEMBUATAN PROGRAM MEWUJUDKAN 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM LINGKUNGAN BELAJAR SD METHODIST 3 PALEMBANG - Sukistini, Anastasia Sri; Pranoto, Stepanus Sigit; Utami, Tresiana Sari Diah; Indriasari, B. A.; Riyanto, Riyanto (Jurnal Abdimas Musi Charitas, 2025)
Purpose: This community service activity was carried out to support the implementation of the "7 Habits of Great Indonesian Children" movement, which aims to shape a golden generation with strong character. The program targets educational institutions at various levels, and in this case, is focused on empowering educators and education staff at SD Methodist 3 Palembang to understand and apply the movement effectively. Design/Methodology/Approach: The activity was conducted through structured socialization sessions and participatory workshops involving all teachers and school staff. The method included concept dissemination, discussion forums, and the formulation of applicable school-based activity plans aligned with the seven habits. Findings: The participants gained a comprehensive understanding of the "7 Habits of Great Indonesian Children" and successfully developed a draft implementation program tailored to the conditions and needs of SD Methodist 3 Palembang. Practical Implications: The movement can be integrated into the school’s character education strategy through systematic and sustainable planning. It strengthens the role of educators in fostering positive behaviors and habits among students. Originality/Value: This activity contributes to national character education by equipping primary school educators with concrete knowledge and practical tools to instill foundational habits that support student development. The collaboration model between higher education institutions and primary schools also enhances the impact of character-based educational movements.